PELAKSANAAN PEMOLISIAN DI KOMPLEKS PERMATA CENGKARENG - Dwi Arie Wibowo (Jurnal Kriminologi Indonesia, 2011)
Kompleks Permata or so-called Kampung Ambon is well known as a drugs related place. There was tending violent crime also presence of cock-fight gambling. On March 2009, there were build a police station right in the middle of Kompleks Permata. This research provides a description about policing implementation in Kompleks Permata. Researcher applies qualitative approach, quasi-experimental methods with before and after design. There are three indicators which researcher utilizes in purpose to compare policing in time before and after the police station have been built; (1) society partnership, (2) crime prevention, (3) problem solving. This research discover that there are no significant difference in policing between before and after time the police station have been built. Here is an advice related to policing implementation problems in Kompleks Permata, there is should be held an effective community development in order to solves existing problems together.